The effect of strain-rate sensitivity on dynamic response of impulsively loaded sandwich beam. Issue 20 (18th October 2019) - Yang, Li-Hong; Qu, Jia; Yu, Guo-Cai; Yang, Jin-Shui; Wu, Lin-Zhi
ABSTRACT: A theoretical analysis method is developed to study dynamic responses of clamped strain-rate-sensitive sandwich beam subjected to impulsive loading based on Cowper and Symonds constitutive model. The front sheet of the sandwich beam is normally loaded by a uniformly distributed impulse. The effect of strain-rate sensitivity is characterized by an influence factor independent of time history but related to initial impact kinetic energy. The relationship between this influence factor and initial kinetic energies is analyzed for three different materials. The dynamic response process of sandwich beam is divided into two stages: core compression stage and overall beam deformation stage. The strain-rate sensitivity of materials is considered only in the second stage of dynamic response analysis. From the comparison of the results of sandwich beam with that of monolithic beam, we can conclude that this method of introducing influence factor to characterize the strain-rate-sensitive effect is valid to analyze the dynamic responses of impulsively loaded sandwich beams.